Wideband and polarisation‐independent antireflection coating using metamaterials. Issue 5 (1st October 2020) - Sepehripour, Fahimeh; Karimi, Parisa; Khavasi, Amin
Abstract : Here, the authors propose a new approach for realising wideband and polarisation‐independent antireflection coating, based on a metamaterial composed of a subwavelength array of metallic pillars with a square cross‐section. The effective impedance of the array can be duly adjusted by the size and distance of the pillars. As such, the authors design the effective impedance of the antireflection coating to be the geometrical mean of the impedance of upper and lower media and choose its height to be quarter of operating wavelength. Doing so, the reflection vanishes at the desired frequency and fractional bandwidth of 56% is achieved with a criterion of 10% reflectance (the refractive index of the substrate is assumed to be 4). Importantly, the proposed structure is symmetric in both directions. Thus, in contrast to prior arts, it is not sensitive to the polarisation of the incident wave at normal incidence. In addition to that, it is designed based on a multilayer Chebyshev matching transformer of transmission line theory, which potentially increases the bandwidth of the antireflection up to 107%, albeit at the expense of pass‐band ripples. This structure can be used from very low frequencies up to the infrared regime by appropriate scaling.